(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Policies and regulations with the nature of the multispecies and multigear fleets of small-scale can cause a decrease in the catch in each fishing area. Fishing fleet clustering can provide more effective and efficient information for management actions. This study aims to identify clustering fleets of small-scale fisheries based on the similarity of catch, income, and operational costs. The research method uses survey methods, primary and secondary data types, and the determination of respondents by purposive sampling technique. Analysis of data used is descriptive analysis and Square Euclidean Distance. The results show that the highest catch, income and operational costs during the west season and transition 1 are purse seine, east season and transition 2 are lift net, while the lowest in west season to transition 2 is drift gillnet fleet. In general, in the west season there are 3 large cluster groups, transition season 1 has 2 large cluster groups, east season there are 3 large cluster groups, transition season 2 has 4 large cluster groups. This results showed that the number and structure fleets of small-scale fisheries clustering always changes in every season.